2009
DOI: 10.1039/b901025d
|View full text |Cite
|
Sign up to set email alerts
|

Patch clamping on plane glass—fabrication of hourglass aperture and high-yield ion channel recording

Abstract: Planar patch-clamp has revolutionized ion-channel measurement by eliminating laborious manipulation from the traditional micropipette approach and enabling high throughput. However, low yield in gigaseal formation and/or relatively high cost due to microfabricated processes are two main drawbacks. This paper presents patch clamping on glass substrate-an economical solution without sacrificing gigaseal yield rate. Two-stage CO(2) laser drilling methodology was used to generate an hourglass, funnel-like aperture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…3(b), the aperture's edges are rounded and have a lip. Although not as pronounced as in the micromachined hourglass shape (Chen et al 2009), this lip may enhance contact area between the cell membrane and polyimide surface, thus improving seal formation and allowing the recording of high-quality signals.…”
Section: Electrophysiological Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3(b), the aperture's edges are rounded and have a lip. Although not as pronounced as in the micromachined hourglass shape (Chen et al 2009), this lip may enhance contact area between the cell membrane and polyimide surface, thus improving seal formation and allowing the recording of high-quality signals.…”
Section: Electrophysiological Results and Discussionmentioning
confidence: 99%
“…Gigaseal formation is poorly understood, but published studies on planar patch-clamp systems have suggested the importance of several parameters. The surface making contact with the cell membrane should be smooth, clean and hydrophilic; it should have a high area of contact with the cell membrane, thus favoring an hourglass shape for the aperture (Chen et al 2009, Lehnert et al 2007, Sordel et al 2006. The type of cells, their passage number and minimal debris in the cell suspension also play a role.…”
Section: Electrophysiological Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1b)): the glass pipette was replaced by a membrane having microfeatures (called apertures) mimicking the tip of the pipette [2]. Apertures have been fabricated in silicon dioxide (SiO 2 ) [3][4][5], silicon nitride (Si 3 N 4 ) [6], quartz/glass [7,8], poly(dimethylsiloxane) (PDMS) [9,10] and polyimide (PI) [11]. However, the available planar patch-clamp systems have only been applied to isolated cells in suspension.…”
Section: Introductionmentioning
confidence: 99%